Development of Early Startup Companies' Valuation Model Based on Android Mobile Application: The Angel Investor's Perspective - Candra Sari, Ratna; Wahyu Dewanti, Patriani; Fajar, M. Andryzal; Priantinah, Denies; Pranesti, Arin (JOIV : International Journal on Informatics Visualization, 2022)
This research aims to develop a valuation model for early startup companies based on an Android mobile application (Valuasi app). This application aims to help early startups to evaluate their company performance. This research method uses the research development method. The first stage is to develop a startup valuation model by determining the criteria using the multi-criteria decision making (MCDM) method and weighting the criteria using the simple additive weighting (SAW) method. The instrument and the weight determination of the valuation model have been validated from the perspective of angel investors, practitioners, and academics. The second stage is developing an Android-based startup valuation model application. The third stage is an evaluation by the users of the application. Using the Unified Theory of Acceptance and Use of Technology (UTAUT) model, the results show that a potential user's intent to use the application is affected by the performance expectancy and social influence toward the application. This valuation model is expected to help early startup companies conduct business valuations, so they can attract investors, especially angel investors. In addition, the results showed that there was a positive response from users in using the 'Valuasi app', which was indicated by the positive and significant effect of performance expectations on usage intentions, and a positive and significant influence on social influence and behavioral intentions on user behavior. This research shows that 'Valuasi app' can be used to assess start up valuation. However, further improvements are needed to support application facilities so as to increase the ease of using the "Start Up Valuation App" application